High-dose versus low-dose block-and-replace treatment for a first episode of Graves’ disease - Arnaud Smolders; Aglaia Kyrilli; Stefan Matei Constantinescu; Bernard Corvilain; Chantal Daumerie; Maria-Cristina Burlacu (European Thyroid Journal)
Objective: The optimal treatment with antithyroid drugs (ATDs) for a first episode of Graves’ disease (GD) remains controversial. Methods: Retrospective, two academic centres study of newly diagnosed GD between 1990 and 2022, treated with ATD in block-and-replace (B+R) regimen for at least 12 months and followed up for at least 1 year after ATD discontinuation or until disease relapse. Sixty patients received high-dose B+R (HD) with fixed ATD dose maintained during the study, and 60 patients received low-dose B+R (LD) with lower ATD dose adjusted during the study. Results: Baseline characteristics were similar in both groups. The point-prevalence of euthyroidism was not different between HD and LD (38 vs 47%, P = 0.460 at 6 months, 69 vs 82%, P = 0.194 at 12 months, 70 vs 78%, P = 0.370 at 18 months, respectively). At 18 months, 27% HD vs 38% LD (P = 0.242) had thyroid eye disease. There were no differences in the number or type of ATD-related adverse events (AE) (no AE 73 vs 78%, P = 0.707). LD received mean lower ATD dose (15.3 ± 4.2 vs 30.0 ± 0.0 mg/day, P < 0.001) and lower levothyroxine dose (72.6 ± 16.7 vs 100.6 ± 24.5 μg/day, P < 0.001). After a first course of ATD, 63% of HD patients and 60% of LD patients relapsed (P = 0.707) after a median time (interquartile range) of 11.0 (18) vs 7.0 (19) months (P = 0.109). Conclusion: We observed similar relapse rates in patients with a first episode of GD receiving up to 50% less ATD and 30% less levothyroxine dose than high-dose B+R regimen.